Postoperative evaluation of Er:YAG laser, piezosurgery, and rotary systems used for osteotomy in mandibular third-molar extractions - YILMAZ, HANİFE NURAY (CHURCHILL LIVINGSTONE, 2021)
Objective: This study compared patient postoperative pain, swelling, and trismus after usage of rotary instruments, piezosurgery, and Er:YAG lasers in mandibular third-molar extraction. Materials and methods: This prospective study was executed with class II and position B vertically impacted mandibular third molars. Patients were divided into three groups according to the osteotomy system used to remove retentive bone: rotary instruments, piezosurgery, and Er:YAG laser. Postoperative painwas evaluated using VAS questionnaires at 12 h, 24 h, 48 h, and 7 days after procedures. Trismus was evaluated by measuring the distance between the maxillary and mandibular incisors at maximum mouth opening, and comparing preoperative measurements with those for postoperative days 2 and 7. Analyses of swelling were carried out via a stereophotogrammetry system. Operation times were measured using a digital stopwatch from the initial incision to the final suture. Results: There were no statistically significant differences between the groups in terms of pain, trismus, or swelling (p > 0.05). Pain persisted more in the rotary instrument group 24 h later (0 +/- 1.3; p = 0.001). The pain scores obtained after 48 h for the piezosurgery (1.81 +/- 2.29) and rotary (2.2 +/- 2.12) groups were observed at 24 h in the laser group (2.19 +/- 1.52). The mean operation time was highest using the laser (19.1 +/- 3.85 min; p = 0.001) and lowest using rotary instruments (9.88 +/- 2.97 min; p = 0.001). Conclusion: Piezosurgery and Er:YAG laser are good alternatives to rotary instrument systems in third-molar extraction, but both systems are slower than traditional rotary instruments. (C) 2020 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd. All rights reserved.
Keywords: Er:YAG laser; Piezosurgery; Stereophotogrammetry; 3RD MOLAR SURGERY; REMOVAL; INSTRUMENTS; BUR